Divergent philosophical commitments in neuroscience: Evidence from a global survey - Fabián Navarro-Peña; Gonzalo Arrondo; Nathaniel F. Barrett; Francisco Güell; Gabriel Madirolas; José Ignacio Murillo; Javier Sánchez-Cañizares; Javier Bernacer (Proceedings of the National Academy of Sciences, 2026)
The mind–brain relationship is a foundational yet underexplored dimension of contemporary neuroscience, shaping research framing, data interpretation, and public communication. We conducted a large-scale international survey of 2,657 neuroscientists to assess their views on the mind–brain problem, free will, and the future of the discipline. Our results reveal a complex and sometimes paradoxical worldview. While 64% of participants endorse reductive physicalism—the view that mental activity is fully reducible to brain function—only 17.5% reject free will. Despite estimating that current knowledge covers only a limited portion of brain structure and function (30%), respondents express marked optimism about the future of neuroscience, including the prospect of fully understanding the human being and mental disorders through neuroscience, and even achieving mind reading and mental uploading. A principal component analysis identified five latent dimensions, some of which vary systematically across sociodemographic and disciplinary factors. These findings indicate that neuroscientists hold diverse philosophical commitments that diverge from common narratives of hard determinism. The prevalence of neuroessentialist views further highlights the need for sustained interdisciplinary dialogue to address the conceptual, ethical, and societal implications of neuroscientific progress.